Cultural Heritage as a Potential for Tourism Development Based on Local Potential and Oriented towards Sustainable Development - Muhammad Yudi Ansyah; Eny Haryati; Priyanto Priyanto (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
The city of Malang holds heritage-city status with dozens of cultural-heritage buildings, yet this historical capital has not yet translated into commensurate tourism benefits; visits are brief, economic benefits are uneven, and a number of buildings are at risk of change of function. This study aims to map the cultural-heritage potential of Malang City, assess how far its use is aligned with the principles of sustainable development and local potential, and formulate a tourism-development strategy that unites conservation, community empowerment, and sustainability. The study population consisted of heritage-tourism stakeholders in Malang City, with a purposively selected sample of ten informants covering government officials, experts, conservation communities, business operators, residents, guides, and tourists. Data were collected through in-depth interviews, observation, and documentation, then analysed using an interactive model—data reduction, display, and conclusion drawing—followed by a SWOT analysis to formulate strategy. The results show that Malang's cultural heritage has strong appeal, particularly because it combines buildings, kampongs, culinary traditions, and residents' stories, but its use is not yet sustainable: the tourism experience remains shallow, economic benefits are uneven, community participation is limited to implementation, environmental pressure is rising, and governance and data remain fragmented. The recommended strategy is to build a coordinated, community-based cultural-heritage tourism ecosystem, comprising an integrated heritage route, a visitor-data platform, multilingual interpretation, adaptive-reuse guidelines, carrying-capacity control, and a cross-stakeholder forum. The study concludes that conservation and utilisation can proceed together when managed in an integrated way that places the community as the principal actor.